2022
DOI: 10.1021/acs.jpclett.1c04085
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Barrier of Ion Transport in Poly(ethylene oxide)–Li7La3Zr2O12 Composite Electrolytes Illustrated by 6Li-Tracer Nuclear Magnetic Resonance Spectroscopy

Abstract: Fundamental understanding of the lithium-ion transport mechanism in polymer–inorganic composite electrolyte is crucially important for the rational design of composite electrolytes for solid-state batteries. In this work, the Li+ ion transport pathway in a model composite electrolyte of PEO containing sparsely dispersed LLZO (PEO–LLZO) was studied by an advanced characterization technique, i.e., 6Li-tracer NMR spectroscopy. By analyzing the 6Li distribution within the PEO–LLZO composite at the end of the disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…In addition, the interfacial barrier formed between active fillers and the polymer matrix affects the transport pathway of lithium ions as well. He et al 72 found that the increased current density caused a reduced lithium ion flux through the LLZO particles in the PEO-LiTFSI-LLZO (5 wt%) composite, because higher current densities enhanced the ion transport barrier between LLZO and the polymer matrix, and then confined the transfer of lithium ions from the polymer phase to LLZO. As active fillers have higher ionic conductivity than polymer matrices, there should be a great improvement in the ionic conductivity with an increase in the filler content, and the ionic conductivity is expected to be even close to that of the active fillers, when the content of active fillers is high enough.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interfacial barrier formed between active fillers and the polymer matrix affects the transport pathway of lithium ions as well. He et al 72 found that the increased current density caused a reduced lithium ion flux through the LLZO particles in the PEO-LiTFSI-LLZO (5 wt%) composite, because higher current densities enhanced the ion transport barrier between LLZO and the polymer matrix, and then confined the transfer of lithium ions from the polymer phase to LLZO. As active fillers have higher ionic conductivity than polymer matrices, there should be a great improvement in the ionic conductivity with an increase in the filler content, and the ionic conductivity is expected to be even close to that of the active fillers, when the content of active fillers is high enough.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…In addition, the interfacial barrier formed between active fillers and the polymer matrix affects the transport pathway of lithium ions as well. He et al 72 found that the increased current density caused a reduced lithium ion flux through the LLZO particles in the PEO–LiTFSI–LLZO (5 wt%) composite, because higher current densities enhanced the ion transport barrier between LLZO and the polymer matrix, and then confined the transfer of lithium ions from the polymer phase to LLZO.…”
Section: Ion Transport Pathwaysmentioning
confidence: 99%
“…In conclusion, Li-ion transport channels gradually transition and modified related to the content of LLZO. Similarly, He's team [108] utilized the modified 6 Li-tracer NMR method to study the composite electrolyte's Liion transport mechanism qualitatively and quantitatively by measuring the exchange of a single equivalent 6 Li isotope at various current densities. It was displayed that the 6 Li ratio of LLZO was improved in 6 Li NMR spectra at 0.025 C; however, at the current densities were 0.1 C and 0.3 C, the 6 Li content was consistent with the original, demonstrating that the transport channel in LLZO has priority only at low current density.…”
Section: + Pathways Within Llzo/polymer Scesmentioning
confidence: 99%
“…[19,20] Recently, 6 Litracer NMR spectroscopy was applied and demonstrated great superiority in tracking the Li-ion transport pathways in polymerceramic composite electrolytes. [21][22][23][24] It is disclosed that manipulating the transmission barrier (space charge layers) between two phases and the local electric field is highly effective for highefficiency Li-ion transport. The effect of space-charge layers on the ionic transport over the interface can also be exposed using NMR dynamics and two-dimensional NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%